The holy tongue: The play on words in Andean cosmology - Randall, Robert (1987)
In the last twenty years we have seen a flourishing of Andean linguistic studies, characterized, as Cerrón-Palomino [1985: 509] says, by "unusual developments, completely revolutionizing the knowledge in force until then...". Despite so many advances, however, very few philological studies have been based on ethnohistorical sources and/or modern ethnology, a fact lamented by Espinoza Soriano [1982], who highlights the richness of such sources, giving a brief review of Andean ideas and concepts extracted from them.